Analysis of Funds for Community Empowerment Programs for Economic Development - Setianingsih, Novie Astuti; Aalin, Elmi Rakhma (Jurnal Analisis Bisnis Ekonomi, 2020)
This research is concerned to analyze the possible economic impacts caused by infrastructure development. This research focuses on a community empowerment program called Prodamas, from the City of Kediri, East Java. Research methods using descriptive quantitative analysis. The analysis of this study is to observe the allocation of Prodamas funds through how much the remaining funds per RT are returned to the City Government of Kediri. The results of his research are an increase in absorption of production allocation funds from year to year which can indicate an increase in infrastructure, social and economic development. It can be concluded that there is an increase in the community empowerment program (Prodamas) which occurred in the City of Kediri. It also reflected the large impact caused by the economic development of the community with the existence of Prodamas.